#TITLE_ALTERNATIVE# - PRASETYA SUHERMAN PUTRA (NIM: 15109034); Pembimbing: Dr. Ir. S. Hendriatiningsih, MS.; Dr. He, ANDIKA
The development in this era is causing 3D spatial information needed for various purposes. Those purposes are needed quickly, therefore the mapping survey is required to be faster. This research was carried out using a device called Terrestrial Laser Scanner (TLS), which can answer those needs. TLS is a new device that has its own method. The device is able to record points in large quantities with high accuracy in a relatively short time, thus impacting on cheaper survey cost and also providing measurements of the points in a 3D coordinate system (x,y,z). TLS has advanced components inside, including camera and using Terrestrial Laser Scanning method, which makes TLS an efficient survey device. In the research process, the control point data from GPS measurements is collected and scanning of road and parcel of land objects. The data processing stage includes registration which uses registration natural point feature method, filtering, georeferencing using indirect method two-stage approach, and modeling. Results are obtained in the form of a 3D solid model. Analysis is conducted by comparing the model’s level of detail to the photograph’s level of detail, also the distance measure of 3D solid model is compared to the distance measure using distometer. The tstudent statistical test is used to test the average distance measure of the 3D solid model against the average distance measure of the distometer. The conclusion is that a mapping survey using TLS is able to create a 3D model of the path and parcel of land object, the 3D model’s distance measure is equal to the field’s distance measure, and the model’s level of detail reaches 3rd floor.